2001
DOI: 10.2175/106143001x139182
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal Pathogen Removal by Alternative On‐Site Wastewater Treatment Systems

Abstract: Subsurface-flow constructed wetlands, sand filters, and peat filters near Duluth, Minnesota, were studied to determine their seasonal performance for removing pathogens from wastewater. Influent was a high-strength septic tank effluent (mean values of 5-day biochemical oxygen demand, total nitrogen, and total phosphorus were 294, 96, and 15 mg/L, respectively) at the Natural Resources Research Institute's alternative treatment system test facility in northern Minnesota. Each treatment system was inoculated wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
29
0

Year Published

2003
2003
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(32 citation statements)
references
References 25 publications
3
29
0
Order By: Relevance
“…This is a mean removal efficiency of 98% (range 90-100%), with the 75th percentile removal efficiency 98.2%. Although this level of pathogen removal is consistent with the removal rates reported for experimental peat columns treating septic tank effluent [14], it is far greater than the level available by either sand or gravel filters [33].…”
Section: Parameter Phsupporting
confidence: 84%
“…This is a mean removal efficiency of 98% (range 90-100%), with the 75th percentile removal efficiency 98.2%. Although this level of pathogen removal is consistent with the removal rates reported for experimental peat columns treating septic tank effluent [14], it is far greater than the level available by either sand or gravel filters [33].…”
Section: Parameter Phsupporting
confidence: 84%
“…[1] One of the greatest concerns about groundwater contamination is the occurrence of enteric pathogens, which have been found to survive in septic tanks and then move along with percolating wastewater through the disposal field and soil to reach groundwater. [2,3] The need to remove pathogens from wastewater is long recognized. Pathogenic contamination causes disease outbreak and contributes to background disease rate around the world and most seriously impacting the developing world.…”
Section: Introductionmentioning
confidence: 99%
“…In fact, it has been reported that wetlands constructed with peat media removed a larger amount of Salmonella than a wetland constructed with sand media (Pundsack et al, 2001). Ushijima et al (2013) used a filter bed of fine soil (1-4 mm diameter) in a horizontal subsurface flow wetland and reported removal of 5 log 10 units for E. coli and 3 log 10 units for MS2 phage, while coarse soil could not remove these microorganisms.…”
Section: Mechanical Filtration and Media/plant Importancementioning
confidence: 99%
“…However, due to high bacterial nitrification of ammonium in aerobic filter beds and to presence of high natural humic and tannic acids, a very small number of constructed wetlands have reported pH as low as 3.7 to 4.7 (Pundsack et al, 2001). This low pH was reported to contribute to greater Salmonella removal (Pundsack et al, 2001).…”
Section: Physical-chemical Factors Of Temperature Ph and Dissolved mentioning
confidence: 99%
See 1 more Smart Citation